2020
DOI: 10.1177/2043820620934209
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between COVID-19 and extended urbanization

Abstract: This commentary focuses on the relationship between extensive forms of urbanization and emerging infectious disease, using empirical examples from the COVID-19 pandemic. Specifically, it examines the role of shifting urban-ecological relationships, infrastructures, and governance dynamics in both giving rise to, and mitigating, the impact of infectious disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 13 publications
1
84
0
7
Order By: Relevance
“…Indeed, fragmented governance, characterized by different priorities, and conflicts between different levels of governance over limited resources is blamed for the limited success in containing the spread of virus in some contexts such as the US and Australia. Such conflicts are partially attributed to the limited local independence and high reliance on the central government for coordinating actions ( Connolly et al, 2020a ; Steele, 2020 ). In fact, while top-down management through multi-level governance systems is essential for coordinating activities, some level of local leadership is needed for taking nimble and timely actions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, fragmented governance, characterized by different priorities, and conflicts between different levels of governance over limited resources is blamed for the limited success in containing the spread of virus in some contexts such as the US and Australia. Such conflicts are partially attributed to the limited local independence and high reliance on the central government for coordinating actions ( Connolly et al, 2020a ; Steele, 2020 ). In fact, while top-down management through multi-level governance systems is essential for coordinating activities, some level of local leadership is needed for taking nimble and timely actions.…”
Section: Resultsmentioning
confidence: 99%
“…The recent pandemic has brought to the fore the issue of urban vulnerability to pandemics and has resurrected interest in this topic. As various forces such as climate change and human encroachment into natural wildlife habitats may increase the frequency of pandemics in the future, better knowledge of the underlying patterns and dynamics of pandemics, their effects on cities, and necessary preparation, response, and adaptation measures is needed ( Connolly et al, 2020a ). In this regard, the recent pandemic offers an unprecedented opportunity to understand how cities might be affected by pandemics and what actions are needed to minimize the impacts and enhance urban pandemic resilience.…”
Section: Introductionmentioning
confidence: 99%
“…54,55 The interaction between COVID-19 and kidney diseases presents strong evidence that CDs and NCDs are closely interlinked. COVID-19 has highlighted the Accepted Article dangers caused by environmental degradation, with increasing encroachment by humans on spaces occupied by non-humans 56 .The RNA sequencing of the current SARS Coronavirus has revealed that it is strikingly similar to the strain found in bats, providing strong support to its zoonotic origin. Air pollution, which been associated with increased transmission of COVID-19, 57 is also emerging as a causative or a strong contributory factor in disease progression of CKD.…”
Section: One Healthmentioning
confidence: 99%
“…Cities are at the heart of the COVID‐19 crisis in terms of transmission, impact, management, and recovery (Connolly, Ali, & Keil, 2020; Nathan, 2020). Not only are city authorities on the frontline (Acuto, 2020a) but cities have been repositioned as key sites of action and as “the ground zero of the Corona crisis” (LeVine, 2020), raising hope and concern about their governance during and beyond the pandemic.…”
Section: Introductionmentioning
confidence: 99%